2013
DOI: 10.1111/psyp.12043
|View full text |Cite
|
Sign up to set email alerts
|

Peak individual alpha frequency qualifies as a stable neurophysiological trait marker in healthy younger and older adults

Abstract: The individual alpha frequency (IAF) of the human EEG reflects systemic properties of the brain, is highly heritable, and relates to cognitive functioning. Not much is known about the modifiability of IAF by cognitive interventions. We report analyses of resting EEG from a large-scale training study in which healthy younger (20-31 years, N = 30) and older (65-80 years, N = 28) adults practiced 12 cognitive tasks for~100 1-h sessions. EEG was recorded before and after the cognitive training intervention. In bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
177
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(202 citation statements)
references
References 85 publications
(200 reference statements)
17
177
3
5
Order By: Relevance
“…The present study supports previous literature suggesting IAPF “is highly stable in healthy adults up to 80 years, not easily modifiable by cognitive interventions alone, and thus qualifies as a stable neurophysiological trait marker” (Grandy et al, 2013b, p. 570). Moreover, the results are not in contrast with preliminary findings in sport that demonstrated a shift in IAPF may occur with physical activity when strong effort and cardio vascular and metabolic processes are involved.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The present study supports previous literature suggesting IAPF “is highly stable in healthy adults up to 80 years, not easily modifiable by cognitive interventions alone, and thus qualifies as a stable neurophysiological trait marker” (Grandy et al, 2013b, p. 570). Moreover, the results are not in contrast with preliminary findings in sport that demonstrated a shift in IAPF may occur with physical activity when strong effort and cardio vascular and metabolic processes are involved.…”
Section: Resultssupporting
confidence: 91%
“…Several studies within the cognitive domain have demonstrated that IAPF values are related to latent cognitive general factors (e.g., Grandy et al, 2013a), are strongly related to hereditability (e.g., Smit et al, 2006) and are not modifiable (e.g., Grandy et al, 2013b). These studies may partially explain the lack of variation in IAPF both at baseline, and pre-and post-task among groups.…”
Section: Discussionmentioning
confidence: 99%
“…We computed the EEG frequency band power using two sets of EEG band distributions -traditional EEG frequency band definitions (theta: 4–8Hz, alpha I: 8–11Hz, alpha II: 11–14Hz, beta I: 14–25Hz, beta II: 25–35Hz, gamma I: 35–40Hz, gamma II: 40–44Hz) and individualized frequency band distribution from individual alpha frequency (IAF) [17, 25]. Concerning about individual differences, theta and alpha ranges were defined from the baseline IAF with the following formula [26].…”
Section: Methodsmentioning
confidence: 99%
“…The iAPF has been found to show considerable heritability (Posthuma et al, 2001;Smit et al, 2006) and stability with respect to cognitive interventions in healthy adults (Grandy et al, 2013b). On the other hand, Angelakis et al (2007) demonstrated that the iAPF can be increased by neurofeedback training in older adults.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 97%
“…It is relatively easy to assess, and thus, has high potential for monitoring within-person changes of neurophysiological integrity from early childhood up to old age (Grandy et al, 2013b). However, although the iAPF has been repeatedly shown to relate to cognitive performance, its relationship to sensorimotor performance has not been investigated so far.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%